Dehumanisasi dan Krisis Kesadaran Hukum di Era Industri Modern: Kajian Sosiologis atas Hilangnya Moralitas dalam Relasi Produksi - Ridwan, Agusriansyah; Febianty, Iranda Nadya; Edisam, Kuswandi Dwi Eri; Amellia, Demitha Selvira; Yulianingrum, Aullia Vivi (Faculty of Law, Diponegoro University, 2025)
The development of modern industrialization has created new tensions in the social structure, which have weakened human values and the moral legitimacy of law. This study aims to analyze the relationship between dehumanization in production relations and the crisis of legal consciousness, as well as to identify the sociological roots of the loss of morality in legal practice in the modern industrial era. This research is useful in enriching the study of legal sociology and providing a conceptual basis for strengthening the humanistic approach in legal policy and education. This study employs a qualitative method with a literature study approach, analyzing both classical and contemporary theories, as well as secondary data from books and national and international journals related to industrialization, dehumanization, and the transformation of legal consciousness. The findings reveal that the transition from mechanical to organic solidarity has shifted the orientation of law toward a more instrumental and formalistic character. Consequently, law has lost its moral essence and its function as a social balancer, being replaced by the logic of productivity and efficiency that generates anomie and weakens the fulfillment of humanistic values within production relations. The implications of this study emphasize the importance of rehumanizing the law through ethics-based legal education, strengthening community participation in the formation and implementation of law, and promoting legal policies that balance economic interests with social justice and human dignity. The recommendation is that it is very important to implement the concept of legal rehumanization based on social solidarity as a transformative solution to the crisis of moral legitimacy in law in the modern industrial era.